An audit of medullary thyroid carcinoma from a tertiary care hospital in northwest India - Chakraborty, Ananda Mohan; Rai, Ashutosh; Pal, Rimesh; Mukherjee, Soham; Dahiya, Divya; Kumar, Rajinder; Saikia, Uma Nahar; Panda, Naresh Kumar; Bhadada, Sanjay Kumar; Dutta, Pinaki (Frontiers in Endocrinology, 2024)
Medullary thyroid carcinoma (MTC) is a rare thyroid malignancy originating from parafollicular C-cells. It accounts for 5%-10% of all thyroid malignancies.An ambispective analysis of pathologically proven MTC presented in a tertiary care hospital in northwest India was performed after considering demography, clinical manifestation, RET mutation status, management, and outcome as denominators.Among 2735 thyroid malignancy cases who presented to our institute in the last 10 years (2012-2022), 78 (3%) had MTC with a mean age of presentation being 43 ± 11 years, and 60% of them were female. The median duration of symptoms was 23 months (IQR 12-36 months). The most common presenting complain was goiter with lymphadenopathy (80.8%). Among the atypical presentations, one each had ectopic Cushing's syndrome, hypertensive crisis in pregnancy due to pheochromocytoma, synchronous chondrosarcoma, and Von-Hippel-Lindau disease spectrum. Median calcitonin and carcinoembryonic antigen(CEA) levels at presentation were 1274 pg/ml (N-64) and 149 ng/ml (N-39) respectively. Twenty-two patients had germline RET mutation-positive, and they presented at a younger age. Majority of the patients presented with stage IV disease. Surgery was the primary modality of therapy. Twentynine patients received radiotherapy and 25 patients received tyrosine kinase inhibitors (TKI).Nine patients received peptide receptor radiotherapy (PRRT) with Lu-177 with neoadjuvant capecitabine. Median progression-free survival (PFS) was 60 months. Patients without structurally and biochemically residual disease and stable disease after the first modality of therapy (Log-rank 11.4; p-0.004) had better PFS. Females (Log-rank: 9.5; p-0.002) had better PFS as compared to male patients.This study showed that MTC comprises 3% of thyroid malignancies with a female preponderance. RET mutation-positive patients had a younger age at presentation. Surgery was the first-line therapy. Radiotherapy, TKI, and PRRT were given as a part of second-line or third-line therapy due to persistent disease and /or disease recurrence. The median progressionfree survival was better in female patients and in patients who had no residual lesions and stable disease after the primary modality of therapy.